Earth System Science in the Anthropocene - Ehlers, Eckart; Krafft, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
Earth System Science in the Anthropocene aims to provide an in-depth perspective and update on special topics in Global Environmental Change in relation to Human Security. It gives an overview on the new Joint Projects of the four International Global Change Programmmes and on research efforts in Germany. It is also an up-to-date report on emerging necessities in Global Environmental Change research as well as suggestions for its future development.
Introduction: The Anthropocene -- Global Change Research in the Anthropocene: Introductory Remarks -- Managing Global Change: Earth System Science in the Anthropocene -- The (3z(BAnthropocene(3y (B-- Sustainability Science -- What about Complexity of Earth Systems? -- Global Change and Human Security -- Climate Change, New Weather Extremes and Climate Policy -- Assessing Human Vulnerability to Global Climatic Change -- Fire Ecology of the Recent Anthropocene -- Disaster Prevention -- Global Environmental Change and Human Health -- Urban Disasters as Indicators of Global Environmental Change: Assessing Functional Varieties of Vulnerability -- Energy in a Sustainable Development Perspective -- Interfaces between Nature and Society -- Integrative Water Research: GLOWA Volta -- Carbon Cycle Research as a Challenge of the Anthropocene -- International Institutions and the Carbon Regime -- Global Environmental Change and Food Systems GECAFS: A new interdisciplinary research project -- Food Security in South Asia -- Scientific Challenges for Anthropogenic Research in the 21st Century -- Scientific Challenges for Anthropogenic Research in the 21st Century: Problems of Scale.s
Keywords: Environment; Geobiology; Ecology; Environmental law; Environmental policy; Geoecology; Environmental geology; Environment; Geoecology/Natural Processes; Biogeosciences; Ecology; Environmental Law/Policy/Ecojustice.; Electronic books